HUBUNGAN SANITASI TPM TERHADAP KEPADATAN KECOA DI PELABUHAN PEMENANG KKP KELAS II MATARAM - Budi Kusumaningrum; Praba Ginandjar; Sri Yuliawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Port Health Office of Class II Mataram in Pemenang port must be freed from vectors including cockroaches. High density of cockroaches may become disease transmission risk factor at port region. This research aims to understand the cockroach density related sanitation food processing facilities at class II Port Health Mataram, Pemenang. It is an analytic observational research by cross sectional approach. Samples in this research were all caught cockroaches in 26 food processing facilities at Pemenang Port. Chi square test result between cockroach density and food processing facilities sanitation (p=0,0001;OR=32,5). There were significant relationship between cockroach density at Pemenang Port and buildings food processing facilities sanitation. It is recommended to those in charge in food processing facilities to always control sanitation and perform cockroach control efforts when cockroach present in those buildings/structures and food processing facilities.